PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA PADA YAYASAN XAVERIUS TANJUNGKARANG - Kurnia, Andreas Nanda; Widiatna, Alexius Dwi (CREDENDUM: Jurnal Pendidikan Agama, 2021)
The transformational leadership style of school principals plays a crucial role in motivating, raising awareness, and inspiring school members to achieve educational goals without feeling burdened. Principal leadership is a key factor influencing teacher performance. This study aims to describe the transformational leadership style of junior high school principals at the Xaverius Tanjungkarang Foundation, assess the performance of their teachers, and determine the influence of principal leadership on teacher performance. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to junior high school teachers at the Xaverius Tanjungkarang Foundation in Lampung. The findings reveal that: (1) the transformational leadership style of the principals is in the very high category, (2) teacher performance is also in the very high category, and (3) the transformational leadership style of the principals has a positive and significant effect on teacher performance. These results highlight the importance of effective leadership in enhancing educational quality through improved teacher performance.